PREPARATION OF FINANCIAL STATEMENTS MSMES RUMAH BASO ACI 180 BASED ON SAK EMKM - Vivi Vitriah; Vicky Dzaky Cahaya Putra (ITB AAS Indonesia Surakarta, 2023)
About company finances that can be used in assessing performance and seeing the company's condition at a certain time. In one period the accounting cycle can be determined according to quarterly or monthly, weekly and daily needs. This research aims to make it easy for MSME owners to prepare financial reports based on existing standards on January 1, 2018. This research is aimed at 180 UMKM Rumah Baso Aci whose financial reports are not prepared based on SAK EMKM. Qualitative descriptive is used in this research which is a case study. The data was collected through documentation, interviews and observation. This research was carried out so that the problems that existed in UMKM Rumah Baso Aci 180 were identified and financial reports were prepared based on existing accounting standards. The results of this study show that the problems faced by MSMEs in preparing financial reports are limited thinking to regulate financial reports and the preparation of financial reports is inadequate due to limited Human Resources (HR). Financial reports based on SAK EMKM namely Notes to Financial Statements, Profit and Loss Reports and Statements of Financial Position.